Performances of methane-powered crawler tractor tested in stationary and field conditions - D. Assandri; E. Cavallo; M. Tamagnone; N. Pampuro (Energy Conversion and Management: X)
Nowadays, global attention is focused on the production and use of renewable energy to combat climate change and achieve energy independence. In this context, the agricultural sector plays a key role by utilizing biogas-upgrading systems from anaerobic digestion to produce biomethane, which can power agricultural machinery.This study aims to evaluate the performance of a methane-powered engine installed on a crawler tractor compared to a conventional diesel-powered crawler of equivalent power. Tests were conducted under static conditions, according to the OECD Code 2, and in real working conditions, simulating two common vineyard operations: pesticide application and grass cutting.In static tests, the methane engine achieved a power output of 47.5 kW, compared to 46.7 kW for the diesel engine, with respective specific fuel consumptions of 230.4 g kWh−1 and 261 g kWh−1. However, under real working conditions, the statistical analysis highlighted significant differences favoring the diesel engine in terms of specific fuel consumption, thermal efficiency, and specific energy consumption. Although the methane engine consistently matched the diesel engine’s power output in all test scenarios, it demonstrated lower efficiency, probably due to methane’s reduced volumetric energy density. This reduction impacted overall performance in real working conditions. These limitations emphasize the challenges methane faces as a fuel, particularly in applications where more frequent refueling is necessary, leading to shorter operational range and reduced autonomy.